Pengaruh teknik perkalian garis (cross-line) pada tahap ketiga teori polya terhadap kemampuan pemecahan masalah matematis - Wulandari, Ayu Dita; Mahfud, Hasan; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2025)
Abstract. This study aims to determine whether there is an effect of the technique of adding lines (cross-line) in the third stage of the Polya theory on the ability to solve mathematical problems. This research is a quantitative research. This study uses a quasi-experimental method through pretest-posttest nonequivalent control group design. This study used two classes, namely as an experimental class that applied the technique of adding lines (cross-line) at the third Polya theory stage, and a control class that applied a tiered addition technique. Data collection is carried out through tests. The validity test was carried out through content validity with expert judgment, external validity with test questions, and construct validity with the CFA test. Data analysis used a simple linear regression test. Prior to treatment, a pretest was carried out to measure students' problem solving abilities in the experimental class and control class. After the treatment was completed, a posttest was carried out to measure students' mathematical problem solving abilities in both classes. Data analysis obtained the following results: the use of the technique of adding lines (cross-line) in the third stage of Polya theory had an influence on students' mathematical problem-solving skills in improving grade IV SD Cluster 3 Arjuna, Mojogedang District, Karanganyar Regency. This has been proven from the analysis of hypothesis testing from the average posttest value of the experimental class of 71.339 and that of the control class of 60.893. Hypothesis testing with simple linear regression showed a significance value of 0.022 <0.05, and showed an effect of 18.5%. Therefore, H0 is rejected and H1 is accepted.